Determination Of Vitamin C And Antioxidant Activity In Fresh Red Guava (Psidium Guajava L.) And Red Guava Commercial Fruit Juices - Khairiyah, Siti; Sinaga, Siti Morin; Putra, Effendy De (Publisher Cv. Inara, 2022)
Red guava (Psidium guajava L.) has various benefits such as overcoming digestive disorders, thrush and dengue fever and can be used for anticancer herbal therapy. Red guava fruit is a fruit with the highest levels of vitamin C compared to other fruits. It contains carotenoid compounds and phenolic compounds that act as antioxidants. Red guava fruit is often processed into fruit juice drinks that are packaged in various types of packaging and distributed commercially so that people can consume red guava fruit more efficiently. Determination of vitamin C levels using the UV-Visible spectrophotometric method and the results obtained that the vitamin C content of red guava commercial fruit juice is higher than fresh red guava juice. Measurement of antioxidant activity of red guava fruit and its commercial fruit juice using ABTS methods. The results obtained in the ABTS method, fresh red guava juice and its commercial fruit juice have very strong antioxidant activity (IC50 < 50 µg/mL).